SARS-CoV-2 antibody prevalence among healthcare workers: A cross-sectional study at a quaternary healthcare center in Saudi Arabia - Hala A. Amer; Hassan A. Abdallah; Haifa S. Alkheledan; Shaimaa H. Alzarzour; Ahmad Shrahily; Hani Tamim; Saleh A. Alqahtani; Ziad A. Memish (Elsevier, 2022)
Background: The objective of this study was to determine the seroprevalence of SARS-CoV-2 antibodies among Healthcare Workers (HCWs). Methods: We carried out a cross-sectional study among 3644 HCWs at King Saud Medical City (KSMC) during the last two weeks of December 2020. A Google form survey was used to collect data on demographics, underlying health conditions, job duties, infection control competencies, COVID-19 exposure history, symptoms, and confirmed infections. Findings: 26.5% demonstrated seropositivity to SARS-CoV-2 antibodies, 10-fold higher than the national seroprevalence (2.36) conducted in May 2020. Seropositivity was significantly higher among non-Saudi HCWs and participants who lived outside the hospital dormitory p < 0.0001 and 0.01, respectively). Seropositivity was significantly higher among HCWs who worked on clinical areas of high exposure level, and those who spent longer duration working with patients with COVID-19; p = 0.002 and 0.005, respectively). Conclusion: SARS-CoV-2 infections among HCWs can go unrecognized, which magnifies the importance of complying with universal masking and social distancing directives. Detecting SARS-CoV-2 antibodies in HCWs can help healthcare leaders in considering staff allocations and assignments accordingly.